Recomendaciones de promoción de hábitos saludables y prevención de la hipoacusia neurosensorial en oficiales de obra en la empresa Alca ingeniería S.A.S. (2023)
In this study, strategies were developed for the construction officers of the company Alca Ingeniería SAS, with the aim of promoting healthy habits and preventing sensorineural hearing loss. Sensorineural hearing loss is a chronic hearing condition that affects the ability to perceive sound and can be caused by constant exposure to high levels of noise in the work environment. Therefore, it was necessary to create new strategies to address this problem.